γ-Aminobutyrate Improves the Postharvest Marketability of Horticultural Commodities: Advances and Prospects - Aghdam, Morteza Soleimani; Flaherty, Edward J.; Shelp, Barry J. (Frontiers in Plant Science, 2022)
Postharvest deterioration can result in qualitative and quantitative changes in the marketability of horticultural commodities, as well as considerable economic loss to the industry. Low temperature and controlled atmosphere conditions (low O2 and elevated CO2) are extensively employed to prolong the postharvest life of these commodities. Nevetheless, they may suffer from chilling injury and other physiological disorders, as well as excessive water loss and bacterial/fungal decay. Research on the postharvest physiological, biochemical, and molecular responses of horticultural commodities indicates that low temperature/controlled atmosphere storage is associated with the promotion of γ-aminobutyrate (GABA) pathway activity, with or without the accumulation of GABA, delaying senescence, preserving quality and ameliorating chilling injury. Regardless of whether apple fruits are stored under low temperatire/controlled atmosphere conditions or room temperature, elevated endogenous GABA or exogenous GABA maintains their quality by stimulating the activity of the GABA shunt (glutamate  GABA  succinic semialdehyde  succinate) and the synthesis of malate, and delaying fruit ripening. This outcome is associated with changes in the genetic and biochemical regulation of key GABA pathway reactions. Flux estimates suggest that the GABA pool is derived primarily from glutamate, rather than polyamines, and that succinic semialdehyde is converted mainly to succinate, rather than γhydroxybutyrate. Exogenous GABA is a promising strategy for promoting the level of endogenous GABA and the activity of the GABA shunt in both intact and freshcut commodities, which increases carbon flux through respiratory pathways, restores or partially restores redox and energy levels, and improves postharvest marketability. The precise mechanisms whereby GABA interacts with other signaling molecules such as Ca2+, H2O2, polyamines, salicylic acid, nitric oxide and melatonin, or with phytohormones such as ethylene, abscisic acid and auxin remain unknown. The occurrence of the aluminumactivated malate transporter and the glutamate/aspartate/GABA exchanger in the tonoplast, respectively, offers prospects for reducing transpirational water in cut flowers and immature green fruit, and for altering the development, flavour and biotic resistance of apple fruits.